'I'm like you, and I like what you like' sustainable food purchase influenced by vloggers: A moderated serial-mediation model. (November 2021) - Xu, Zhen; Islam, Tahir; Liang, Xiaobei; Akhtar, Naeem; Shahzad, Mohsin
Abstract: Internationally, researchers have shown an increased interest in customer decision-making regarding sustainable food choices that could be changed through tailored interventions. This study examines how vloggers influence customer purchase intention toward sustainable food. Based on the similarity-attraction theory, we undertook a serial mediation model in which health-related Homophily between vloggers and viewers was related to higher purchase intention of sustainable food via audience participation and parasocial interaction (P.S.I.). In addition, we tested whether these potential relationships were more substantial for young people from higher product-vlogger congruence and lower advertising recognition in the celebrity endorsement context. A statistical analysis of 382 youth questionnaire data from the steaming media platform was tested through the partial least squares structural equation model. The results show that (1) health-related homophily was related to greater audience participation and P.S.I., which, in turn, were related to higher purchase intention of sustainable food; (2) the positive indirect effects of health-related Homophily on purchase intention through audience participation and P.S.I. decrease as the advertising recognition increase, while increase as the product-vlogger congruence increase. These findings highlight the effectiveness of digital celebrity endorsement in young people's choices for sustainable food. Highlights: Health-related homophily is positively related to purchase intention. Audience participation mediates the positive relationship between health-related homophily and para-social interaction. Para-social interaction mediates the positive relationship between health-related homophily and purchase intention. Audience particiaption and para social interaction mediated the relationship between health related homopphily and purchase.